2011
DOI: 10.1371/journal.pone.0017370
|View full text |Cite
|
Sign up to set email alerts
|

ITPKC Single Nucleotide Polymorphism Associated with the Kawasaki Disease in a Taiwanese Population

Abstract: Kawasaki disease (KD) is characterized by systemic vasculitis with unknown etiology. Previous studies from Japan indicated that a gene polymorphism of ITPKC (rs28493229) is responsible for susceptibility to KD. We collected DNA samples from 1,531 Taiwanese subjects (341 KD patients and 1,190 controls) for genotyping ITPKC. In this study, no significant association was noted for the ITPKC polymorphism (rs28493229) between the controls and KD patients, although the CC genotype was overrepresented. We further com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 22 publications
3
67
0
1
Order By: Relevance
“…KD may lead to formation of coronary artery aneurysms and to ischemic heart disease, myocardial infarction and sudden death (Hata and Onouchi, 2009). The link between this ITPKC polymorphism and KD (or resistance to KD treatment) was confirmed in other studies, but others failed to reproduce these results and no association of the ITPKC locus with KD was detected (Burgner et al, 2009;Khor et al, 2011;Kuo et al, 2011;Lin et al, 2011;Onouchi et al, 2013;Peng et al, 2012).…”
Section: Introductionmentioning
confidence: 76%
“…KD may lead to formation of coronary artery aneurysms and to ischemic heart disease, myocardial infarction and sudden death (Hata and Onouchi, 2009). The link between this ITPKC polymorphism and KD (or resistance to KD treatment) was confirmed in other studies, but others failed to reproduce these results and no association of the ITPKC locus with KD was detected (Burgner et al, 2009;Khor et al, 2011;Kuo et al, 2011;Lin et al, 2011;Onouchi et al, 2013;Peng et al, 2012).…”
Section: Introductionmentioning
confidence: 76%
“…The results from a study by Lin et al [63] in another independent medical center in Taipei indicated that the C allele of rs28493229 is associated with KD susceptibility. Recently, new results using meta-analysis showed that the rs28493229 SNP of ITPKC is associated with the susceptibility to KD in the Taiwanese population [39] . Regarding to the controversial results obtained for ITPKC genetic association studies in the Taiwanese population, we attribute them to population migration, due to the increase in genetic diversity between cities in the south or north of Taiwan [39] .…”
Section: Genetic Polymorphisms Of the Itpkc Signaling Pathway In Patimentioning
confidence: 99%
“…For example, a number of genes have been reported to have significant associations with the susceptibility to KD in different populations. For instance, single nucleotide polymorphisms (SNPs) in the monocyte chemoattractant protein 1 (MCP-1) [29] , IL-10 [30][31][32] , CD40L [33] , IL-4 [26] , CASP3 [20,34] , IL-18 [35] , IL-1B [36] , HLA-E [37] , C-C chemokine receptor 5 (CCR5) [38] , and inositol 1, 4, 5-trisphosphate 3-kinase C (ITPKC) [21,39] have been reported to be associated with the development of KD. In early 2011, Shimizu et al [12] first reported that genetic polymorphisms of TGFB2, TGFBR2, and SMAD3 are associated with susceptibility to Kawasaki disease and the development of coronary artery lesions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations